Quantum effects in the radial thermal expansion of bundles of single-walled carbon nanotubes doped with 4He - Dolbin, A.V.; Esel`son, V.B.; Gavrilko, V.G.; Manzhelii, V.G.; Vinnikov, N.A.; Popov, S.N.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The radial thermal expansion αr of bundles of single-walled carbon nanotubes saturated with 4He impurities to the molar concentration 9.4% has been investigated in the interval 2.5–9.5 K using the dilatometric method. In the interval 2.1–3.7 K αr is negative and is several times higher than the negative αr for pure nanotube bundles. This most likely points to 4He atom tunneling between different positions in the nanotube bundle system. Theexcess expansion was reduced with decreasing 4He concentration.